(untitled) (Politeja, 2015)
The Evolution of Institution of Presidency in Political History of Ukraine: Incipience, Powers, Role and Place in the System of Government The author determined phases of formation, powers, role and place of presidency in the government system of Ukraine at different stages of its political development, outlined historiography of presidency’s researches in Ukraine, incrementally structured the evolution of political and legal views about the nature and purpose of the presidency in Ukraine, outlined the factual authority, role and place of presidency in the government system of Ukraine (on Ukrainian ethnic territories) in the first decade of the twentieth century. He also described the influence of the USSR presidency on the characteristics of formation and role of the presidency in post‑Soviet Ukraine as well as revealed the dynamics of presidency in the independent Ukraine, 1991‑2014. The author also found out the problem of institutional inheritance of presidency (including his powers, role and place in system of government) in the context of impact of some historical milestones of Ukrainian statehood in the following historical milestones. As result, the researcher argued that the institution of presidency in Ukraine (including the government system at all) needs to be reformed because of the past institutional, legal and political legacy of the presidency in Ukraine, and given to the experience of presidency in Central and Eastern Europe countries.